2022
DOI: 10.1021/acsami.1c22307
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protein Adsorption Capacity of Macroporous Pectin Particles with High Specific Surface Area and an Interconnected Pore Network

Abstract: There has been much interest in developing protein adsorbents using nanostructured particles, which can be engineered porous materials with fine control of the surface and pore structures. A significant challenge in designing porous adsorbents is the high percentage of available binding sites in the pores owing to their large surface areas and interconnected pore networks. In this study, continuing the idea of using porous materials derived from natural polymers toward the goal of sustainable development, poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…The adsorption isotherm type was determined using a modified version of the previously reported batch equilibrium method. , Adsorption experiments were performed at room temperature (25 °C) with TOCN particles (20 mg/mL) dispersed in the lysozyme solution (50 mL). The initial lysozyme concentration was adjusted to 0.6 mg/mL, and the pH was adjusted to 7.0 with phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption isotherm type was determined using a modified version of the previously reported batch equilibrium method. , Adsorption experiments were performed at room temperature (25 °C) with TOCN particles (20 mg/mL) dispersed in the lysozyme solution (50 mL). The initial lysozyme concentration was adjusted to 0.6 mg/mL, and the pH was adjusted to 7.0 with phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…An automatic specific surface and porosity analyzer is used to obtain the physical property parameters, such as the specific surface area, pore volume and pore size distribution. The specific surface area of Fe/ZrATP (138.256 m 2 /g) is obviously greater than that of ATP (100.37 m 2 /g), which may be because the metal elements Fe and Zr are not only distributed on the surface of ATP but also enter the pores of the concavite in small amounts, increasing the layer spacing of the material and forming a bilayer structure with an increased surface area (Nguyen et al 2022). Then, the specific surface area of Fe/ZrATP increases again due to the uniform load of Fe 3 O 4 , which yields a rough composite surface, as observed from the SEM images in Fig.…”
Section: Characterizationmentioning
confidence: 96%
“…In this study, the macroporous TWC particles were facilely synthesized by a template-assisted aerosol process. The template-assisted aerosol process has been widely employed to produce the macroporous structure of various materials, such as carbon, , silica, , metal and metal oxides, , and natural polymers. , Therefore, the aerosol process may be potentially effective in preparing the macroporous TWC particles with the assistance of lab-made polystyrene latex (PSL) as a template. However, no previous study has reported the particle formation mechanism of macroporous TWC particles via the aerosol route as well as the influence of PSL concentration on the framework thickness between macropores.…”
Section: Introductionmentioning
confidence: 99%